ROS Induced by KillerRed Targeting Mitochondria (mtKR) Enhances Apoptosis Caused by Radiation via Cyt c/Caspase-3 Pathway. (7th March 2019) - Li, Xin; Fang, Fang; Gao, Ying; Tang, Geng; Xu, Weiqiang; Wang, Yihan; Kong, Ruoxian; Tuyihong, Ayixianguli; Wang, Zhicheng
Abstract : During radiotherapy, reactive oxygen species- (ROS-) induced apoptosis is one of the main mechanism of radiation. Based on KillerRed which can induce ROS burst in different cell substructures, here we hypothesized that KillerRed targeting mitochondria (mtKR) could induce ROS to enhance apoptosis by radiation. In this study, empty vector, mtKR, and mtmCherry plasmids were successfully constructed, and mitochondrial localization were detected in COS-7 and HeLa cells. After HeLa cells were transfected and irradiated by visible light and X-rays, ROS levels, mitochondrial membrane potential (Δ ψ m ), ATPase activities, adenosine triphosphate (ATP) content, apoptosis, and the expressions of mRNA and protein were measured, respectively. Data demonstrated that the ROS levels significantly increased after light exposure, and adding extra radiation, voltage-dependent anion channel 1 (VDAC1) protein increased in the mitochondria, while Na + -K + and Ca 2+ -Mg 2+ ATPase activities, ATP content, and Δ ψ m significantly reduced. Additionally, the cell apoptotic rates dramatically increased, which referred to the increase of cytochrome c (Cyt c), caspase-9, and caspase-3 mRNA expressions, and Cyt c protein was released from the mitochondria into the cytoplasm; caspase-9 and -3 were activated. These results indicated that mtKR can increase the production of ROS, enhance mitochondrial dysfunction, and strengthen apoptosis by radiation via Cyt c/caspase-3 pathway.